Homogeneously niobium-doped MoS2 for rapid and high-sensitive detection of typical chemical warfare agents - Jiang, Huaning; Wang, Huaizhang; Shangguan, Yanlei; Chen, Jingfei; Liang, Ting (Frontiers in Chemistry, 2022)
Rapid detection of Chemical Warfare Agents (CWAs) is of great significance in protecting civilians in public places and military personnel on the battlefield. Two-dimensional (2D) molybdenum disulfide (MoS2) nanosheets (NSs) can be integrated as a gas sensor at room temperature (25°C) due to their large specific surface area and excellent semiconductor properties. However, low sensitivity and long response-recovery time hinder the pure MoS2 application in CWAs gas sensors. In this work, we developed a CWAs sensor based on in-situ niobium-doped MoS2 NSs (Nb-MoS2 NSs) via direct chemical-vapor-deposition (CVD) growth. Characterization results show that the high content of Nb elements (7.8 at%) are homogeneously dispersed on the large-area 2D structure of MoS2. The Nb-MoS2 NSs-based CWAs sensor exhibits higher sensitivity (-2.09% and -3.95% to 0.05 mg/m3 sarin and sulfur mustard, respectively) and rapid response speed (78 s and 30 s to 0.05 mg/m3 sarin and sulfur mustard, respectively) than MoS2 and other 2D materials at room temperature. And the sensor has certain specificity for sarin and sulfur mustard and is especially sensitive to sulfur mustard. This can be attributed to the improvement of adsorption properties via electronic regulation of Nb doping. This is the first report about CWAs detection based on two-dimensional (2D) transition metal dichalcogenides (TMDs) sensing materials, which demonstrates that the high sensitivity, rapid response, and low limit of detection of 2D TMDs-based CWAs sensor can meet the monitoring needs of many scenarios, thus showing a strong application potential.